A study on adverse drug reactions of oral anti-diabetic agents in patients with type II diabetes mellitus in Hi-Tech Medical College and Hospital, Bhubaneswar, Odisha, India - Dey, Indrani; Mohanty, Srikanta; Prasad, Anju; Patnayak, Chaitali; Palit, Ratna (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes mellitus is an emerging non communicable, life style disease & the use of anti-diabetics has been increasing. Adverse drug reactions (ADRs) are well known to occur with any class of drugs when used in normal doses for the management of diseases. Anti-diabetic agents are no exception to this. The study of ADRs is the concern of the field known as pharmacovigilance. The objective of the present study was to analyze and describe the patterns of adverse events associated with the use of oral Anti-diabetic agents Methods: A hospital based prospective observational study at Hi-Tech Medical College and Hospital, Bhubaneswar, Orissa. Convenience samples of 266 adult patients, prescribed with oral anti-diabetic agents from October 2016 to November 2018 were selected, out of which 74 patients developed ADRs. Data collected from available prescriptions. The severity assessment is done using the Hartwig and Siegal scale and preventability assessment using modified Schumock and Thornton is done. Results: Study suggests that female predominance in 41 (55.40%) patients with maximum cases of 43.24% in age group of 61-70 years age group. Maximum ADRs reported related to endocrine system seen in 36 (48.67%) patient population. Sulfonylureas 38 (51.35%) shows the largest numbers of ADR. The maximum ADRs reported were probable (56.73%). The severity assessment using the Hartwig and Siegal scale indicated that the majority of the ADRs were 63 (81.63%) as mild cases respectively. Conclusions: This study has provided evidence of monitoring and detecting ADRs and their management through therapeutic interventions which is beneficial in the better patient outcome.